2021
DOI: 10.1002/ece3.7427
|View full text |Cite
|
Sign up to set email alerts
|

Processes that drive the population structuring of Jenynsia lineata (Cyprinidontiformes, Anablepidae) in the La Plata Basin

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…This pattern is frequently observed in species with low dispersal ability (e.g. Briñoccoli et al, 2021) like P. parodii. Our F ST values indicate clear differentiation among the main evolutionary lineages, and the remaining analyses pointed to the spontaneous establishment and long-term persistence of them in micro-refugia.…”
Section: Functional Annotation Of Detected Outlier Snpsmentioning
confidence: 62%
See 1 more Smart Citation
“…This pattern is frequently observed in species with low dispersal ability (e.g. Briñoccoli et al, 2021) like P. parodii. Our F ST values indicate clear differentiation among the main evolutionary lineages, and the remaining analyses pointed to the spontaneous establishment and long-term persistence of them in micro-refugia.…”
Section: Functional Annotation Of Detected Outlier Snpsmentioning
confidence: 62%
“…Smolders et al, 2002;Thalmeier et al, 2021), and fragmenting and disconnecting entire basins (e.g. Briñoccoli et al, 2021) that also impacted the riverbanks and lands around. The Pleistocene impact on P. parodii diversification was highly supported by demographic analysis based on this high-dense genome coverture.…”
Section: Functional Annotation Of Detected Outlier Snpsmentioning
confidence: 99%
“…These endorheic basins are characterized by high diversity of endemic freshwater fishes ( Miquelarena and Menni 1999 ). Briñoccoli et al (2021) observed that the type (endorheic vs. exorheic) of basin played a predominant role in population structure (as well as the altitude at which the rivers were located) in Jenynsia lineata , a small ovoviviparous fish widely distributed throughout the La Plata Basin. As well as in A.…”
Section: Discussionmentioning
confidence: 98%
“…If the time of isolation is long enough, it can result in population genetic differentiation within the species that has been fragmented. But if the time of isolation is even greater, it may eventually lead to allopatric speciation ( Dias et al 2013 ; Jardim de Queiroz et al 2017 ; Briñoccoli et al 2021 ). Finally, to assess whether the IBE is structuring the haplotype network of Acrobrycon species, we measured the altitude in meters above sea level for each site in which specimens of Acrobrycon were collected.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…There are enough examples of consanguineous populations with significant phylogenetic differences. For example, these include populations of char of the genus Salvelinus in the lake and lake-river systems of the Kamchatka Peninsula [47]; the northern slimy salamander (Plethodon glutinosus), living in several southern states of the United States [48]; Jenynsia lineata, which is a small viviparous fish from South America [49]; and the black-throated blue warbler (Dendroica caerulescens), living in North America with northern and southern subpopulations [50]. With the variety of reasons for the disjoining of these populations, it can be assumed that they are characterized by disruptive selection of certain traits and reproductive isolation between extreme forms.…”
Section: Discussionmentioning
confidence: 99%